Effect of Protein Supplementation in the Bee Apis mellifera L. Exposed to the Agrochemical Fipronil - Moreira, Iloran Rc [UNESP]; Barros, Daniel Cb [UNESP]; Lunardi, Juliana S [UNESP]; Orsi, Ricardo O [UNESP] (Universidade Estadual de Feira de Santana, 2021)
Inadequate quantity and quality of proteins in honey bee diet can cause weakening of their colonies and damage their resistance to agrochemical contamination, such as fipronil, which is highly toxic to bees. Thus, we tested the hypothesis if protein supplementation would improve longevity and locomotion of honeybees exposed to fipronil pesticide. Colonies of Apis mellifera Africanized were distributed into Control Group without protein supplementation and Supplemented Group with 25% crude protein provided as a paste form at 100 g per week. After four weeks, frames with sealed brood were removed and kept in an incubator until the emergence of worker bees, which were marked, returned to their hives and recaptured six days later to measure protein concentration in the hemolymph. The bee population development was measured by evaluating frames containing the queen's oviposition from each colony. Also, nursing bees were recaptured exposed by contact to fipronil LD50% (0.009 ± 0.003 μg/bee), and the longevity and motor activity were measured. The results showed that the bee swarms protein supplementation promoted a significant increase in the sealed brood area. However, it did not promote changes in the protein content of the hemolymph. Protein supplementation of bee swarms did not influence the survival of bees exposed to fipronil in the locomotion tests; however, fipronil was toxic to bees and promoted changes in the locomotion of bees.
Keywords: Beekeeping; Neurotoxicity; Nutrition; Protein; Supplementation